The Influence of Reinforcement on Students’ Attitude to study English at SMA Negeri 1 Bontolempangan - Nurdiana, Nika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
The aims of This research is to know the influence of reinforcement on students attitude to study English. This research used descriptive research. From 120 students the research took 40 students as a sample by using random sampling technique. In collecting data, the research used questionnaire, in which the students choosed on of fine response provided. The result of the students answer was analyzed using linker scale to see whether or not there was any influence of reinforcement on the students’ Attitude to study English. The finding of the research revealed that very positive. The result of data analysis showed that the mean score of the positive reinforcement is 95,4%, and the negative Reinforcement is 36,7 %. From the research of data analyst, the researcher concluded the influence of reinforcement on students’ attitude to study English at SMA Negeri 1 Bontolempangan Kabupaten Gowa are it means that the student were very enthusiastic towards the teachers in study English